An Analysis of Commercial Banks’ Lending and Agricultural Growth in Nepal - Lamsal, Mani Ratna; Kanel, Nav Raj; Dahal, Madhav Prasad; Soneja, Sakshi (Economic Review of Nepal, 2025)
Agriculture sector sharing almost one-fourth of GDP and two-thirds of employment remains as one of the crucial economic activities in Nepal. However, it faces persistent challenges in Nepalese economy, including limited access to finance. Commercial banks possess a vital role in addressing these challenges by providing credit to farmers, agribusinesses, and rural enterprises. Despite various policy measures and financial incentives, the effectiveness of commercial banks' lending in promoting agricultural growth remains sufficiently unexplored. This paper intends to fulfil this gap. The prime objective of this paper is to analyze the effects of commercial banks’ lending on agricultural growth in Nepal. The study uses ARDL Bounds Testing approach to measure the impact of commercial banks’ lending on agricultural growth in Nepal by using Time Series data for the period 1994-2023. Necessary data were gathered from three major secondary sources: Nepal Rastra Bank (NRB), Ministry of Finance (MOF), and National Statistics Office (NSO). This study found statistically significant positive relationship between Commercial Banks’ lending and agricultural growth in Nepal. The impact of other control variables used in the study, irrigation and fertilizer, are also positive and significant in this regard. Furthermore, the provision of adequate and easy access to borrowing, irrigation facility, and timely availability of fertilizers could also boost the agriculture growth in Nepal.